Nigeria's freedom of information act: provision, strengths, challenges (2011)
It took well over ten years to pass the Freedom of Information bill into law in Nigeria. It also took the bill three journeys to the National Assembly. This article connects the reluctance of the concerned authorities to pass the bill to the age-long struggle in Nigeria (and elsewhere) between the press, citizens and civil society on the one hand and the government on the other, with the former trying to widen the circumference of government activities that should be made public and the latter trying to shrink the same. The article traces the journeys of the FOI Act, and examines its provisions, first attempts at applying it and the challenges to its full implementation